Hard bargains : the politics of sex - Hirshman, Linda R.; Larson, Jane E. (New York : Oxford University Press, 1998)
"The book examines the factors that have shaped our notions of sex, from Catholic teaching to the theories of Sigmund Freud, and it explores Supreme Court decisions of the last few decades that have revolutionized the politics of sex. And Hard Bargains not only provides a deep understanding of historical and current disputes, but it also offers striking predictions of what sexual bargaining will look like in the future - rape laws replaced by laws of sexual autonomy, adultery subjected to breach of contract action, fornicators responsible for each other's rent, prostitution considered an unfair labor practice. These are a few of the surprising - and surprisingly workable - solutions the authors foresee in the 21st century."--Jacket
Table of Contents; Acknowledgments; 1 Introduction: Sex in Public; Part 1 The Origins of Hard Bargains; Part 2 The Rise and Fall of the Republic of Virtue; Part 3 The Rise and Fall of Libertinism; Part 4 Hard Bargains; Index.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Heterosexuality -- Political aspects; Sex -- Political aspects; Sex -- Political aspects -- History; Sex and law; Sex and law -- History; Sexual ethics -- History; Sex; Hétérosexualité -- Aspect politique; Sexualité -- Aspect politique; Sexualité -- Aspect politique -- Histoire; Sexualité et droit; Sexualité et droit -- Histoire; Morale sexuelle -- Histoire; Sexualité.; sexuality; PSYCHOLOGY -- Human Sexuality; SELF-HELP -- Sexual Instruction; Heterosexuality -- Political aspects; Sex and law; Sex -- Political aspects; Sexual ethics; Heterosexualität; Politik; Sexualität; Recht; Family and Relationships; History